Hepatic Cysts as a Manifestation of Polycystic Kidney Disease (Polycystic Liver Report of 2 Mother-Son Cases) - N Osnaya-Romero; S Conrado; P Dautt (Journal of Nephrology Advances, 2021)
Polycystic kidney disease is an inherited disease that can lead to high blood pressure and kidney failure. In Mexico, 4.5% of patients with kidney failure are carriers of this disease; the liver is another of the organs affected by this disease that can manifest as abdominal pain and a mass effect in the abdominal cavity; we present 2 cases of polycystic kidney and liver disease (mother and child), in addition to describing the clinical manifestations, two different stages of the disease are shown, being a hereditary disease it is suggested that once a case is identified, an abdominal ultrasound is performed to first-degree relatives in search of cystic lesions to indicate preventive measures that help us preserve the overall well-being of the patient.
Keywords: Liver cysts